Health expenditure and economic growth in South-South Geopolitical Zone of Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
A nation with healthy population is considered a healthy nation, hence no amount of resources spent on the health sector is considered too much. This research seeks to evaluate the impact of health expenditure on economic growth in Cross River and Akwa Ibom State of Nigeria. Four objectives were formulated to guide and direct the study. The objectives were to investigate the relationship between gross fix capital formation, total health expenditure, government health expenditure, health output funding and Gross Domestic Product growth in CrossRiver and Akwa Ibom State of Nigeria from 1980-2019 . The ordinary least square regression analysis was employed as the estimating technique to test the impact of health funding on economic growth of Cross River and Akwa Ibom States respectively. The findings showed that there exist a significant relationship between gross fix capital formation, and gross domestic product growth, there exist a significant relationship be total health expenditure and gross domestics product growth in Cross River and Akwa Ibom State. Also government healthexpenditure and health output funding exert a significant impact on Gross Domestic Product growth(GDPGR) in Cross River and Akwa Ibom State of Nigeria. The study recommended that increase in health expenditure provision be expanded in order to increase productivity in both States.
Keywords: Health expenditure; Economic growth; Output and Productivity